BOTANICAL COMPOSITION AND FORAGE PRODUCTION UNDER RUBBER PLANTATIONS DURING THE DRY SEASON - D. D., Puspitasari,; Trisnadewi, A. A. A. S.; Suarna, I W. (Jurnal Peternakan Tropika, 2024)
The provision of forage is an absolute requirement for developing ruminants, both small and large ruminants. Forage plants that grow in plantation areas, especially forages that grow under rubber plants, have not been optimally utilized by the community. The study aimed was to determine the botanical composition and yield of forage under rubber plantations in Pangyangan Village, Pekutatan, Jembrana, Bali with coordinates 08. 42911° N and 114. 84904° East with an altitude of 29 m and sampling in September and October 2023. The method used in this research is survey method and direct measurement and observation in the field. Forage production was measured by actual dry weight method using 1 m × 1 m quadrat on flat and sloping land. The results showed that the diversity of vegetation under rubber plantations taken in 30 throws was 11 species, namely Stenotaphrum secundatum, Desmodium triflorium, Mikania cordata, Paspalum conjugatum, Forb, Tracycharpus, Spagneticolla, Lophospermum, Commelina, Sanicula, and S. jamaicensis. The dominating forage under rubber plantations on flat and sloping land collection is S. secundatum. The research was conducted on flat land with light intensity of 60,20% and 53,54% on sloping land. Based on the research it can be concluded that the composition of plants in rubber plantations in Pangyangan Village, Pekutatan, Jembrana, Bali includes 11 species on flat land and 9 species on sloping land, with the most types of grasses and forbs. The total fresh weight production of forage produced on flat and sloping land was 4.2 tons ha-1 and the total dry weight was 1.9 tons ha-1.